THE IMPLEMENTATION OF ONE STOP INTEGRATED SERVICES (PTSP) AT LOCAL GOVERNMENT LEVEL AND IT’S KEY SUCCES FACTORS - Johannes - (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
The establishment of PTSP (One Stop Integrated Service) that required to all the local governments in Indonesia is expected could solve the broad efficiency problems in managing business license and practice. Until 2012, the amount of PTSP both in Provincial and Regencies level is 497 units. As the matter of fact, Local government policy on the establishment of PTSP is varied, it is determined by local government policy and their internal environment. The performance of PTSP however according to independent report indicates that PTSP function is not optimal yet. The government was worried that the implementation will not fulfill the substance of PTSP service and also worried about the business climate wouldn’t be changed. This research has two purposes: 1) to explore the PTSP performance in local government perspective and 2) to identify the key success factor implementation in the level of Regencies and City in order to accelerate the implementation succeeded. In order to manage the two purposes, research was implemented by collecting data in two ways: using data through survey and integrating data by qualitative method that collected through benchmarking. Survey has conducted through 10 local governments in Province of Jambi in 2010 and it is enriched by quantitative survey especially in Jambi City. While qualitative survey that took in form of benchmarking activities was conducted over three successful local governments in implementing PTSP in National Level, they are the Regency of Sragen, Sidoarjo and Jembrana. Furthermore, deep interview was practiced with Technical Team and some key persons that involved in managing business license. The method used to analysis data mainly is qualitative method that purposed to enrich previous findings. This method is used to reveal more facts that could be used by local government to implement PTSP. The research results reveals some key success factors: 1) licenses are not fully aligned to PTSP, 2) poor of top management comittment 3) lack of innovation, 4) poor coordination, 5) lack of user enlighten and 6) designed information system is not well implemented.